Antibacterial and antibiofilm activity of Abroma augusta stabilized silver (Ag) nanoparticles against drug-resistant clinical pathogens - Kumar, Sachin; Khan, Haris M.; Husain, Fohad Mabood; Ahmad, Rafiq; Qais, Faizan Abul; Khan, Mo Ahamad; Jalal, Mohammad; Tayyaba, Uzma; Ali, Syed Ghazanfar; Singh, Amardeep; Shahid, Mohammad; Lee, Byeong-Il (Frontiers in Molecular Biosciences, 2023)
Infectious diseases remain among the most pressing concerns for human health. This issue has grown even more complex with the emergence of multidrug-resistant (MDR) bacteria. To address bacterial infections, nanoparticles have emerged as a promising avenue, offering the potential to target bacteria at multiple levels and effectively eliminate them. In this study, silver nanoparticles (AA-AgNPs) were synthesized using the leaf extract of a medicinal plant, Abroma augusta. The synthesis method is straightforward, safe, cost-effective, and environment friendly, utilizing the leaf extract of this Ayurvedic herb. The UV-vis absorbance peak at 424 nm indicated the formation of AA-AgNPs, with the involvement of numerous functional groups in the synthesis and stabilization of the particles. AA-AgNPs exhibited robust antibacterial and antibiofilm activities against methicillin-resistant Staphylococcus aureus (MRSA) and vancomycin-resistant Enterococci (VRE). The MIC values of AA-AgNPs ranged from 8 to 32 µg/mL. Electron microscopic examination of the interaction of AA-AgNPs with the test bacterial pathogens showed a deleterious impact on bacterial morphology, resulting from membrane rupture and leakage of intracellular components. AA-AgNPs also demonstrated a dose-dependent effect in curtailing biofilm formation below inhibitory doses. Overall, this study highlights the potential of AA-AgNPs in the successful inhibition of both the growth and biofilms of MRSA and VRE bacteria. Following studies on toxicity and dose optimization, such AgNPs could be developed into effective medical remedies against infections.